2023
DOI: 10.1051/0004-6361/202245618
|View full text |Cite
|
Sign up to set email alerts
|

DESI mock challenge

Abstract: Context. We present a novel approach to the construction of mock galaxy catalogues for large-scale structure analysis based on the distribution of dark matter halos obtained with effective bias models at the field level. Aims. We aim to produce mock galaxy catalogues capable of generating accurate covariance matrices for a number of cosmological probes that are expected to be measured in current and forthcoming galaxy redshift surveys (e.g. two- and three-point statistics). The construction of the catalogues s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 188 publications
0
2
0
Order By: Relevance
“…A series of numerical simulations have been compared at the halo level to assess the robustness of numerical simulation methods (Grove et al 2022), while new techniques have been developed to suppress the effects of sample variance in these N-body simulations using approximate mocks (Ding et al 2022). New high-fidelity mock galaxy catalogs have also been developed with mass resolution sufficient to resolve dark matter subhaloes for the BGS sample (Safonova et al 2021), while various techniques have been developed to produce mock catalogs over volumes much larger than possible with N-body simulations (Balaguera-Antolínez et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A series of numerical simulations have been compared at the halo level to assess the robustness of numerical simulation methods (Grove et al 2022), while new techniques have been developed to suppress the effects of sample variance in these N-body simulations using approximate mocks (Ding et al 2022). New high-fidelity mock galaxy catalogs have also been developed with mass resolution sufficient to resolve dark matter subhaloes for the BGS sample (Safonova et al 2021), while various techniques have been developed to produce mock catalogs over volumes much larger than possible with N-body simulations (Balaguera-Antolínez et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…While EZmocks relies on the Zel'dovich approximation (Zel'dovich 1970), PATCHY and BAM rely on ALPT, including tidal field corrections (Kitaura & Hess 2013). It has been shown that such methods can, to a great extent, correct the bias introduced by approximate gravity solvers in the nonlinear and non-local bias description (see the application of BAM to galaxy catalogues, Balaguera-Antolínez et al 2023).…”
Section: Introductionmentioning
confidence: 99%